Modelling Aggregate Labour Demand - Ross Hutchings; Michael Kouparitsas (The Australian Government, The Treasury, 2012)
We derive a conditional long run labour demand equation via a representative firm level profit maximising problem, where production takes place according to a constant elasticity of substitution (CES) production function. This theoretical framework is augmented by cyclical explanatory variables to form an error correction model, which is then estimated using standard econometric methods. Estimates of important labour demand parameters, such as the elasticity of substitution between capital and labour, are consistent with previous Australian studies.
Keywords: J01; J23; J50; 330; labour demand; technical change; production function